Danger Signs of Pregnancy on Compliance with Antenatal Care Visits in the Mamuju Community Health Center Work Area - Susanti, Susanti (International Journal of Health Sciences, 2023)
Pregnancy is the period starting from conception until the birth of the fetus. Normal pregnancy lasts 280 days (40 weeks or 9 months 7 days). Pregnant women's knowledge about danger signs in pregnancy is one of the factors in forming attention to prevent danger from occurring in pregnancy. A mother's good knowledge of the danger signs of pregnancy will make the mother care and motivated to have her pregnancy checked. Pregnant women's compliance with ANC visits aims to monitor the condition of the mother and fetus, in particular early detection of problems that will occur in pregnancy so that appropriate action can be taken for complications that will occur during pregnancy. This study aims to determine the relationship between the level of knowledge of pregnant women about the danger signs of pregnancy and compliance with Antenatal Care visits among pregnant women in the Mamuju Community Health Center Work Area. Method: This research is descriptive correlation with a cross sectional approach. The sample was 50 pregnant women in the Mamuju Community Health Center Working Area taken using convenience sampling or accidental sampling techniques with a total sample of 50 pregnant women. Research Results: There is a relationship between pregnant women's knowledge about the danger signs of pregnancy and compliance with pregnancy visits.